Implementation Of Murabahah Financing In Syariah Banking In Indonesia - Siska Handayani; Dela Syahputri; Mawaddah Warohmah (Fox Justi : Jurnal Ilmu Hukum, 2025)
Moment This study related to financing contract murabaha Still seldom done , by because That researcher need do assessment about studies literature as as Wrong One method study in researching financing contract murabaha on banking sharia. For know How product financing murabaha walk in every - each banking sharia in Indonesia. The method used in study This use method qualitative and methods library research . Financing Murabahah is one of product lots of financing used in Islamic banking in Indonesia. Financing ; murabahah give significant contribution​ to inclusion Islamic finance and development economy people in Indonesia. Research This expected can give outlook for manager Islamic banking in increase quality service financing as well as for regulators in compile more policies​ support development industry Islamic banking.